Elizabeth Grosz. Becoming Undone: Darwinian Reflections on Life, Politics, and Art. Durham: Duke UP, 2011. viii + 264 pp. - Vera Coleman (Studies in 20th & 21st Century Literature, 2015)
Review of Elizabeth Grosz. Becoming Undone: Darwinian Reflections on Life, Politics, and Art. Durham: Duke UP, 2011. viii + 264 pp.
Keywords: Darwinian evolution; feminism; art